1999
DOI: 10.1002/hep.510290445
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen class II and III alleles and severity of hepatitis C virus-related chronic liver disease

Abstract: Hepatitis C outcome is likely related both to viral factors and host's immune responses. We correlated the severity of liver disease with human leukocyte antigen (HLA) genes (C4A, C4B, TNFA, TNFB, DRB1, DRB3, DRB4, DRB5, DQA1, DQB1, TAP1, and TAP2) in three groups of subjects: 99 patients with chronic hepatitis, 41 asymptomatic carriers, and 179 uninfected controls. Patients with grade/stage 3 to 4 hepatitis significantly differentiated for their low frequency of alleles TNFB*1, DRB1*1104, and DRB3*03, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 64 publications
(83 reference statements)
4
88
1
Order By: Relevance
“…27 This apparent lack of agreement among studies may reflect both viral and study group heterogeneity and/or the influence of specific polymorphisms in immunoregulatory genes in linkage disequilibrium with the HLA class II alleles. 26,37 Evidence from the study presented here and others may lead to the identification of crucial T-cell epitopes presented by HCV 1b-infected cells, which stimulate virus clearance.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…27 This apparent lack of agreement among studies may reflect both viral and study group heterogeneity and/or the influence of specific polymorphisms in immunoregulatory genes in linkage disequilibrium with the HLA class II alleles. 26,37 Evidence from the study presented here and others may lead to the identification of crucial T-cell epitopes presented by HCV 1b-infected cells, which stimulate virus clearance.…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, the DRB1*1104 and DQB1*0301 alleles have been found by many groups to occur with significantly greater frequency in those individuals who had a self-limiting HCV infection. 23,26,35,36 However, DRB1*1104 is reported to have an association with viral persistence in a recently reported investigation. 27 This apparent lack of agreement among studies may reflect both viral and study group heterogeneity and/or the influence of specific polymorphisms in immunoregulatory genes in linkage disequilibrium with the HLA class II alleles.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…71,72 Studies of HCV progression or severity of disease A total of 44 studies were found to address the topic of host genetics and HCV progression, severity or activity of disease, and have largely been inconsistent. 16,18,27,29,32,34,37,39,47,[68][69][70]80, There is a trend with DRB1*11 alleles and less severe liver disease. Asti 68 reported an association between DRB1*1201 with less severe liver disease (OR not reported) as well.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 99%